Education and family counseling: certain aspects of cultivating positive daily thinking in adults and children from practical philosophy perspective - Cuznețov, Larisa (CEP USM, 2024)
The article represents a theoretical and applied study that follows the strategic line and doctrinal axis of many works by the author regarding the education and enculturation of the family through the valorization of reflection, the moral action of individuals in the context of counseling focused on the development of positive daily thinking in adults and children. Additionally, here is presented and explained a set of principles, conditions and strategies for family education and counseling, which have been scientifically grounded and correlated with essential orientations from the perspective of social psychology, positive psychology, practical philosophy and complex ontological counseling of the family. Some trends in enhancing the moral climate within the postmodern family are analyzed and methods for building well-being, happiness and improving the quality of family life are specified. In this context, the results of an opinion survey conducted on a structured sample of adults, young family members, and middle-aged individuals (420 subjects aged 25-50) are provided, followed by interpretations, conclusions, and practical recommendations for cultivating positive daily thinking.

Articolul reprezintă un studiu teoretico-aplicativ care urmează linia strategică și axa doctrinală a multor lucrări a autoarei privind educația și enculturația familiei prin valorificarea reflecției, acțiunii morale a persoanei în contextul consilierii axate pe dezvoltarea gândirii cotidiene pozitive la adulți și copii. La fel, sunt expuse și explicate un ansamblu de principii, condiții și strategii de educație și consiliere a familiei, care au fost științific fundamentate și corelate cu câteva orientări esențiale din perspectiva psihologiei sociale, a psihologiei pozitive, filosofiei practice și consilierii ontologice complexe a familiei. Au fost analizate unele tendințe de eficientizare a climatului moral din cadrul familiei postmoderne și s-au precizat modalitățile de edificare a bunăstării, fericirii și sporirii calității vieții familiale. În acest context, am oferit rezultatele unui sondaj de opinii, efectuat pe un eșantion structurat de adulți, familiști tineri și de vârstă medie (420 subiecți de 25 - 50 ani), urmat de interpretări, concluzii și recomandări practice de cultivare a gândirii cotidiene pozitive.
Educația și consilierea familiei: unele aspecte de cultivare a gândirii cotidiene pozitive la adulți și copii din perspectiva filosofiei practice
Keywords: education; counseling; family; positive daily thinking; practical philosophy; educație; consiliere; familie; gândire cotidiană pozitivă; filosofie practică